Community-Based Public Service Transformation: A Qualitative Perspective from the Field - Andriastuti, Komang Tri Putri; Fatmawati, Fatmawati; Rizky, Alifia Ainun (Jurnal Ilmiah Ilmu Administrasi Publik, 2025)
This study explores the transformation of community-based public services as a paradigm shift from traditional bureaucracy toward collaborative governance in Indonesia. Grounded in the theories of New Public Service (R. B. Denhardt & Denhardt, 2003), Co-Production (Alford, 2016), and Public Service Logic (Osborne et al., 2018), this research emphasizes that citizens are not merely recipients of services but active partners in creating public value. The study aims to understand the collaborative practices between government and communities in public service delivery and the social factors influencing their success. Employing a descriptive qualitative approach, the research was conducted in Makassar City through in-depth interviews, field observations, and document analysis focusing on innovative programs such as Lorong Wisata (Tourism Alley), Community Waste Bank, and Jagai Anakta’ (Child Protection Program). The findings reveal that community participation has reshaped the relationship between government and citizens into an equal partnership that produces more adaptive, inclusive, and sustainable services. Beyond administrative efficiency, this transformation strengthens social solidarity, economic independence, and public trust in government institutions. The key success factors lie in social capital—mutual cooperation, a sense of belonging, and networks of trust within the community. Nevertheless, challenges persist in bureaucratic capacity, uneven participation, and program sustainability. The study concludes that community-based public service transformation represents not merely an administrative innovation but a social process that deepens participatory democracy at the local level.